Ethical Issues in Canadian Gastroenterology: Resluts of a Survey of Canadian Gastroenterology Trainees - Kenneth Malhotra; Clifford A Ottaway (Canadian Journal of Gastroenterology)
BACKGROUND: Specialty-specific bioethical education is a mandated component of gastroenterology training programs in Canada, but no gastroenterology-specific bioethical curriculum is available.